THE ROLE OF THE PSYCHOLOGIST IN PRESCHOOL EDUCATIONAL INSTITUTIONS - Davronova Sevinch Alisherovna (Ta’lim innovatsiyasi va integratsiyasi, 2025)
Abstract: This article examines the essential role of psychologists in preschool educational institutions in supporting the holistic development and well-being of young children. Psychologists contribute by assessing developmental milestones, identifying emotional and behavioral issues, collaborating with educators and parents, and designing intervention programs tailored to individual needs. Their involvement ensures that children receive early psychological support, which is crucial for fostering healthy cognitive, social, and emotional growth. The study highlights best practices and challenges faced by psychologists working in preschool settings.